Early Reperfusion After Brain Ischemia Has Beneficial Effects Beyond Rescuing Neurons. Issue 8 (August 2017) - Tachibana, Masaki; Ago, Tetsuro; Wakisaka, Yoshinobu; Kuroda, Junya; Shijo, Masahiro; Yoshikawa, Yoji; Komori, Motohiro; Nishimura, Ataru; Makihara, Noriko; Nakamura, Kuniyuki; Kitazono, Takanari
Abstract : Background and Purpose—: Recent studies show that successful endovascular thrombectomy 6 to 12 hours after stroke onset enhances functional outcomes 3 months later. In this study, we investigated the effects of reperfusion after ischemia on repair processes in the ischemic areas, as well as on functional recovery, using mouse stroke models. Methods—: We examined time-dependent histological changes and functional recovery after transient middle cerebral artery occlusion of different durations, including permanent middle cerebral artery occlusion, using the CB-17 (CB-17/lcr-+/+Jcl) mouse strain, which has poor pial collateral blood flow. Results—: Large microtubule-associated protein 2-negative areas of neuronal death were produced in mice subjected to ≥60 minutes of ischemia followed by reperfusion on day 1, while restricted microtubule-associated protein 2-negative regions were observed in mice subjected to a 45-minute period of ischemia. A substantial reduction in microtubule-associated protein 2-negative areas was observed on day 7 in mice given early reperfusion and was associated with better functional recovery. Klüver–Barrera staining demonstrated that white matter injury on day 1 was significantly lesser in mice with reperfusion. Immunohistochemistry and electron microscopy revealed that a greater number of endothelial cells were present in the infarct areas in mice with earlier reperfusion and were associated with a more rapid recruitment of platelet-derived growth factor receptor β-positive pericytes and subsequent intrainfarct fibrosis. Early reperfusion also resulted in a greater accumulation of glial fibrillary acidic protein–positive astrocytes in peri-infarct areas. Peri-infarct astrogliosis was attenuated in platelet-derived growth factor receptor β heterozygous knockout mice. Conclusions—: Early reperfusion after ischemia enhances the survival of endothelial cells and pericytes within ischemic areas even after the infarct is established, resulting in efficient intrainfarct fibrosis and peri-infarct astrogliosis. These effects might be associated with efficient peri-infarct reorganization and functional recovery. Abstract : Supplemental Digital Content is available in the text.